Literary and art, socio-political magazines in Siberia in 1920–1930s - E. V. Evdokimova (Библиосфера, 2013)
The article characterizes literary-artistic and socio-political Siberian journals in 1920–1930, their classification is proposed, the reasons affecting the duration of the release of printed publications are identified.